O videoclipe e a linguagem mobile como estratégia do processo de ensino-aprendizagem de língua inglesa no ensino médio - Saldanha, Soraya Rozendo Vancini (2017)
The English Language learning, mainly for the ones who are interested in being active part of this more and more internationalized and connected society, besides indispensable, brings benefits that may follow the whole life of an individual. Such learning adds information and abilities which are and will be useful for the living and interaction in the globalized world we live in, world that has the English Language as the main mediatory in its speeches. The English Language teaching, specifically in the Brazilian Elementary and High schools, has been changing and adjusting to transformations through the centuries and, for the last twenty years at least, has been facing the digital inclusion. Our students today, engaged in the digital and technological world, bring on a reaction to the teachers, who should update strategies for a better teaching-learning process. So far, we have seen several individual and collective attempts to adapt schools to the technological world, also bringing this technological world to the schools. Reflecting about all those needs and trying to lead to a more significant learning to our students, this paper reports an English Language teaching proposal with the help of the musical language together with mobile technology and the creation of a video clip. Our aim, besides motivating our students, is to provide room for the development of their creativity, in order to seek their own learning process. We proposed ourselves a challenge to demonstrate that the use of technology inside the classrooms is more available than we may think, once the students can use their own mobiles as supporting means in this teaching-learning process.